Activation of the Mesencephalic Trigeminal Nucleus Contributes to Masseter Hyperactivity Induced by Chronic Restraint Stress - Zhao, Ya-Juan; Liu, Yang; Wang, Jian; Li, Qiang; Zhang, Zhou-Ming; Tu, Teng; Lei, Rong; Zhang, Min; Chen, Yong-Jin (Frontiers in Cellular Neuroscience, 2022)
Psychological stress is commonly accepted to be closely associated with masticatory muscle disorder, which is the main symptom of temporomandibular disorder (TMD). Previous studies have confirmed that exposure to stress may cause masticatory muscle hyperactivity. However, the central mechanism underlying this process remains unclear. The mesencephalic trigeminal nucleus (Vme), which resides in the brainstem, is the primary afferent center for masticatory proprioception and plays a key role in oral–motor movements by projecting to the trigeminal motor nucleus (Vmo). Therefore, the present study was designed to examine the role of Vme neurons in masseter overactivity induced by chronic stress. We found that subjecting mice to restraint stress (6 h/d) for 14 days caused significant anxiety-like behavior, obvious masseter overactivity, and markedly enhanced electrophysiological excitability of Vme neurons. By using anterograde tract tracing combined with immunofluorescence staining methods, we observed vesicular glutamate transporter 1 (VGLUT1)-positive glutamatergic projections from the Vme to the Vmo. Moreover, CRS elevated the expression of VGLUT1 and choline acetyltransferase (ChAT) in Vmo. Furthermore, administration of VGLUT1-targeted short hairpin RNA (shRNA) into the bilateral Vme significantly suppressed the enhanced overexcitability of Vme neurons, downregulated the overexpression of VGLUT1 and ChAT in the Vmo, and attenuated the elevated overactivity of the masseter caused by chronic restraint stress. Taken together, we showed that chronic restraint stress can excite neurons in the Vme, enhancing glutamatergic excitatory projections from the Vme to the Vmo and resulting in masseter muscle overactivity. These findings provide us with a novel central mechanism underlying the correlation between psychological factors and TMD.